The Legitimacy of the Business of Business Schools: What's the Future? - WILSON, David C. (Institutional Knowledge at Singapore Management University, 2012)
The purpose of this paper is to examine some challenges facing business schools and their continued legitimacy. Particular attention is paid to the problems of accreditation, regulation and rankings and how these constrain strategic choice. The paper builds on existing literature to provide an analytical overview of the challenges currently facing business schools. The paper assesses the current context of business schools and assesses to what extent they are becoming less relevant both in terms of practice and theories. It suggests changes business schools might make in order to increase relevance. The paper suggests that business schools should change their central concerns to issues of central relevance to society and to policy. A wide range of such topics, ranging from climate change to exogenous events, is suggested.